Students' Perceptions of Learning Using Powtoon Based on Gender in SMP/MTS - Fajriana, Fajriana; Safriana, Safriana; Nurdin, Nurdin (Malikussaleh University, Aceh, Indonesia, 2022)
Perception is an individual observation or process giving meaning as a result of observations about an object, event, and so on through his five senses, which is obtained by inferring information and interpretation of messages so that someone can provide feedback about the good or bad or the positive and negative of it. The use of animation media in learning other than providing many conveniences, there are also obstacles, causing various student perceptions. Students' perceptions of the use of learning media can be seen by gender. This study aims to determine students' perceptions of learning using animation/powton in SMP/MTs based on gender. Based on the data collected, this research is descriptive with a qualitative approach. The data collection method in this study used a questionnaire in collecting data from primary and secondary sources. In this study, the primary data was the result of a perception survey through a questionnaire conducted to SMP/MTs students. In contrast, secondary information is obtained from a literature review regarding online learning systems and virtual classes. The data analysis technique uses percentages. The results of data analysis are presented descriptively in the following subchapter. Based on the results of research and discussion, it has been known that students' perceptions of learning mathematics using Powton media are perfect. Both male and female students positively perceive learning mathematics by using Powton-based learning media in SMP/MTs. Students get an average student answer of 100% and fall into the